Dengue hepatic severity score: A glimmer to the clinician - Murmu, Sapan Kumar; Mishra, Nihar Ranjan; Nayak, Bijan Kumar (Indian Journal of Child Health, 2018)
Introduction: Recent studies from India and Thailand show that dengue infection was the most compelling cause of acute hepatic failure in children contributing to 18.5% and 34.3%, respectively, and till now, there is no proper dengue severity score based on the hepatic dysfunction, i.e. laboratory as well as clinical hepatic parameters. Objective: The objective of this study was to develop a new dengue hepatic severity score (DHSS) based on only hepatic dysfunction parameters. Methods: The present cross-sectional analytical study was conducted in the Department of Paediatrics, Burla, Sambalpur, Odisha, from November 2015 to October 2017 after getting the institutional ethical clearance. A total of 76 cases selected as per predefined inclusion and exclusion criteria, categorized into three groups after taking written informed consent of their legal hare. Relevant hepatic parameters (both clinical and laboratory) were collected, and data were finally analyzed using receiver operating characteristic curve to get a cutoff value for each group. Results: The cutoff value of DHSS of ?7 between Group 1 and Group 2 evidenced by area under the curve (AUC)=99.6% with 95% confidence interval (CI) (95.6–100%), sensitivity - 100%, specificity - 94.6%, and a cutoff ?18 between Groups 2 and 3 exhibited by AUC=100% with 95% CI (94.6–100%), sensitivity - 100%, and specificity - 94.6%. Hence, the DHSS is formulated as ?6 (no severe hepatic dysfunction), 7–17 (severe), and ?18 (very severe). Mean duration of hospitalization in days between three groups of hepatic dysfunction was statistically significant as evidenced by one-way ANOVA; F (2, 73)=19.83, p=0.000. Conclusion: DHSS system will help the primary health caregiver for triaging, early recognition, and prompt management to prevent additional deterioration.